The Problems of Inheritance Distribution in Contemporary Society: An Analysis of Social Change and the Concept of Justice in Islamic Law - Pujianto; Rihhadatul Aisy Fauziyyah; Naila Rahma Fitria; Okta Dini Fitria; Shelly Marshelina Lubis (STIS Sultan Fatah, 2026)
Social changes occurring in contemporary society have generated various issues in inheritance distribution practices, including changes in family structures, the increasing economic role of women, legal pluralism, and the emergence of new forms of wealth resulting from technological developments. These conditions indicate that inheritance issues are not merely normative in nature but are also shaped by evolving social dynamics. This study aims to analyze the dynamics of social change affecting inheritance distribution practices in contemporary society and to examine the concept of justice in Islamic law as a normative framework for explaining contemporary inheritance issues. This research employs normative legal research with a qualitative approach based on library research. The study applies conceptual, statutory, and comparative approaches, while the data are analyzed using descriptive-analytical content analysis. The findings reveal that contemporary inheritance issues are consequences of changing social contexts that influence how society understands and implements Islamic inheritance law. The concept of justice in Islamic law is not merely normative but is also oriented toward public welfare and the balance of rights and obligations among heirs. This study emphasizes that the relevance of Islamic inheritance law in modern society lies in its ability to respond contextually to social dynamics without neglecting the fundamental principles of Islamic law.